2018
DOI: 10.1136/sextrans-2017-053381
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for oropharyngeal gonorrhoea in men who have sex with men: an age-matched case–control study

Abstract: The finding that oropharyngeal gonorrhoea was associated with a higher number of sexual partners but not specific sexual practices highlights the need for further research in the area of gonorrhoea transmission to define the probability of transmission from specific sex acts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
47
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 32 publications
(50 citation statements)
references
References 28 publications
3
47
0
Order By: Relevance
“…The scarcity of nonpathogenic Neisseria within other bodily niches makes it unlikely that the skin, genital or anorectal site act as an intermediate in this transfer process. As already noted, different types of evidence suggest that pathogenic Neisseria species can be transmitted by kissing [6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Our findings support to the idea that the genus Neisseria can be transmitted by kissing.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…The scarcity of nonpathogenic Neisseria within other bodily niches makes it unlikely that the skin, genital or anorectal site act as an intermediate in this transfer process. As already noted, different types of evidence suggest that pathogenic Neisseria species can be transmitted by kissing [6,[9][10][11][12][13][14][15][16][17][18][19][20][21][22][23]. Our findings support to the idea that the genus Neisseria can be transmitted by kissing.…”
Section: Discussionsupporting
confidence: 90%
“…Several studies have found that kissing is a risk factor for meningococcal disease [9][10][11] or carriage [12][13][14][15] among students. Likewise, N. gonorrhoeae can be readily cultured from saliva [16][17][18], saliva use as a lubricant is a risk factor for rectal gonorrhea [19], kissing [20][21][22] as well as having a main partner with pharyngeal gonorrhea [23] may be risk factors for pharyngeal gonorrhea and a mathematical transmission model showed that oro-oral transmission is essential to generate the actual prevalence of gonorrhea among MSM [6].…”
Section: Introductionmentioning
confidence: 99%
“…The second study by Cornelisse et al . was an age‐matched 1:2 case–control study conducted among 531 MSM in Melbourne in 2015 . Similarly, the study found that men who kissed their casual partners in the last three months were 2.2 (95% CI: 1.3 to 3.6) times more likely to have oropharyngeal gonorrhoea than those who did not kiss their casual partners in the univariable analysis.…”
Section: Resultsmentioning
confidence: 95%
“…'s and Cornelisse et al . 's study measured kissing as part of sexual practices and did not investigate kissing without sex as a risk factor. The third study by Chow et al .…”
Section: Resultsmentioning
confidence: 99%
“…As syphilis transmission gathers pace among men having sex with men (MSM) populations, epidemiologists are increasingly looking to understand the interaction between social and behavioural dynamics, as seen in Schneider et al 5 On the other wide of the world, an Australian case control study of oropharyngeal gonorrhoea in MSM showed an association with higher partner numbers, but none with specific behavioural practices 6…”
mentioning
confidence: 99%